451. Evaluation of Exposure History in Healthcare Personnel with Coronavirus 2019 Disease. (31st December 2020) - Silva, Sandra; Mana, Thriveen; Bhullar, Davinder; Tabor, Beatrice; Donskey, Curtis
Abstract: Background: During the Coronavirus Disease 2019 (COVID-19) pandemic, many healthcare personnel (HCP) have developed COVID-19. However, there is uncertainty regarding whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was acquired at work versus in the community. Methods: We conducted a cohort study to examine exposure history of personnel with COVID-19 infection or asymptomatic carriage in a VA healthcare system. High-risk exposures were classified based Centers for Disease Control and Prevention criteria. Results: Of 578 personnel tested, 49 (8%) had nasopharyngeal swabs with positive PCR results, including 45 (92%) with and 4 (8%) without COVID-19 symptoms. Of the 49 cases, 21 (43%) had a documented high-risk exposure at work, including 14 exposures to COVID-19 patients and 7 exposures to colonized or infected personnel. Exposures to infected patients most often were a result of delays in recognition of COVID-19 due to atypical presentations. Exposures to personnel with COVID-19 most often involved activities such as meals when facemasks were not worn. Most cases occurred among nurses (26, 53%) and administrative personnel (10, 20%); only 3 physicians developed COVID-19. No cases occurred in personnel working on COVID-19 wards. All personnel had mild or moderate disease. Conclusion: Forty-three percent of healthcare personnel with COVID-19 had prior high-risk exposures at work. Improved detection of patients with atypical presentations and efforts to reduce high-risk contacts among personnel may reduce the risk for acquisition of SARS-CoV-2. Disclosures: All Authors : No reported disclosures